Detection of postpartum women anemia and its impact on their offspring in Zhejiang Province, China - He, Mengjie; Huang, Lichun; Zou, Yan; Xu, Peiwei; Su, Danting; Zhao, Dong; Han, Dan; Zhang, Ronghua (Frontiers in Nutrition, 2025)
BackgroundInformation on the prevalence of postpartum women anemia is scarce in China, as well as its impact on their offspring. This study aimed to explore the influencing factors of anemia and the impact on the offspring.MethodsA cross-sectional study was conducted among 977 women within 2 years postpartum in 10 sites from 2016 to 2017 in Zhejiang Province, China. Information on demographics, nutrient supplementation and diet was collected. Whole blood hemoglobin, serum ferritin and transferrin receptor were assessed for all women and whole blood hemoglobin was assessed in offspring. The multivariate logistic regression was used to assess the determinants of anemia and the impact on the offspring by calculating odds ratio (OR) and its 95% confidence interval (95%CI).ResultsAmong 977 participants, 144 (14.74%) had anemia. Regression analysis showed that women intaking iron supplements during pregnancy (0.549, 0.350 ~ 0.860), and intaking sufficient red meat (0.647, 0.437 ~ 0.958) had lower rates of anemia, while women wo had anemia during pregnancy (2.754, 1.844 ~ 4.113 for mild anemia, and 3.815, 1.564 ~ 9.309 for moderate or severe anemia), had postpartum over 7 months (1.717, 1.112 ~ 2.650), with abnormal serum ferritin (11.931, 4.846 ~ 29.379) and excessive transferrin receptor levels (1.817, 1.050 ~ 3.145) had higher rates of anemia. Moreover, maternal anemia significantly increases the rate of anemia in offsprings, with ORs being 1.456 (0.994 ~ 2.133) for mild anemia, and 2.961 (1.242 ~ 7.058) for moderate or severe anemia, respectively.ConclusionThe status of anemia in postpartum women was severe and its impact on the anemia of their offspring should be noted. It is highly necessary to strengthen the regular monitoring of hemoglobin levels in pregnant and postpartum women, as well as implement targeted dietary interventions and suggest to intake dietary supplements if necessary.